Treatment Modalities For Plantar Fasciitis - Mirza, Raof R. (Sulaimani Journal for Pure and Applied Sciences, 2012)
Heel pain due to Plantar Fasciitis is a common presentation to the consultation clinic in Sulaimani Rheumatology center out of 242 painful heels x-rayed 198 had calcaneal spure, which means 81,8% of all patients. 150 patients with Plantar Fasciitis treated with either injections of heel from medial route with either 40mg of methylprednisolone plus 2% xylocain or 2cc of 2% xylocain or 6 sessions of pulsatile ultrasound. All treatment modalities were effective on relieving pain on short term bases, but treatment with steroid plus xylocain was more effective regarding the degree of pain relief and the number of patients improved.
Keywords: Plantar Fasciitis treatment modalities